Korelasi Pengetahuan Dan Sikap Ibu Pascaoperasi Sesar Tentang Mobilisasi Dini - Istiawati, Ni Wayan; Mastryagung, Gusti Ayu Dwina; Sri Ariani, Ni Komang (WOMB Midwifery Journal, 2024)
The delivery via cesarean section carries a high risk of infections, including surgical wound infections, uterine infections, and postpartum infections, which, if not properly managed, can contribute to maternal mortality rates. One effective way to mitigate the risk of such complications is through early mobilization. A lack of understanding among mothers regarding early mobilization may result in reluctance to engage in it, thereby impeding the wound healing process. This study aims to determine the relationship between the level of knowledge and attitudes of mothers post-cesarean operation concerning early mobilization at Banggai Regional General Hospital. This research employs a correlational design with a cross-sectional approach. The sample was selected using a purposive sampling technique, comprising a total of 44 participants who met the inclusion and exclusion criteria. The statistical test utilized is the Spearman rank test. The study results indicate that 88.6% of post-cesarean mothers possess a good level of knowledge about early mobilization, and 93.2% demonstrate a positive attitude toward it. Data analysis reveals that there is a relationship between knowledge and maternal attitudes regarding early mobilization knowledge  (0.000 < α = 0.05). Based on this study, the higher the level of mothers' knowledge about early mobilization, the more positive their attitude toward engaging in it, with the aim of accelerating the wound healing process after delivery.